A novel endoscopic treatment for ureteric remnant hemorrhage post laparoscopic radical nephrectomy. (June 2012) - Michael, Amanda; Sheridan-Jonah, Anna; Kovac, Jason R.; Allard, Christopher B.; Matsumoto, Edward D.
Abstract Laparoscopic radical nephrectomy is commonly used to treat renal masses. Given the ubiquitous presence of this technique, rare complications are becoming more commonplace. It is thus essential that practicing urologists be aware of all possible complications as well as the novel management approaches that exist. This report presents a situation in which a patient developed rapid-onset, postoperative gross hematuria. This complication is rare and multiple sources of bleeding must be considered. In the situation reported here, the ureteric remnant was the cause of the unremitting gross hematuria. While others have described surgical exploration as the primary treatment, the authors were successful in using a minimally invasive endoscopic approach with fulguration and instillation of a fibrin sealant. Indeed, they propose that the endoscopic approach described herein may be considered first line in cases of unremitting gross hematuria originating from the ureteric remnant.